A survey of management of congenital nasolacrimal duct obstruction by pediatric primary health care providers in Spain - Galindo-Ferreiro, Alicia; Palencia-Ercilla, Teresa; Ferreira, Livia Mendoza [UNESP]; Galvez-Ruiz, Alberto; Zornoff, Denise C. M. [UNESP]; Khandekar, Rajiv; Schellini, Silvana A. [UNESP] (SAGE Publications, 2017)
Purpose: To survey the management of congenital nasolacrimal duct obstruction (CNLDO) by pediatric primary health care providers in Spain. Methods: This was a descriptive study using a web-based questionnaire to evaluate the perceptions of the members of the Pediatric Primary Care Society in Castilla-León, Spain (APAPCYL), regarding management of CNLDO. The questionnaire contained 14 direct questions and was sent by e-mail to all the pediatricians. All the responses were analyzed by the frequency of occurrence and percentages. Results: Ninety physicians responded to the questionnaire. Massage 2 or 3 times a day was the initial treatment advised by 60.47% of pediatricians. Nearly half of the pediatricians recommended continuing massage until symptoms resolved. Fewer than 50% of children required referral to an ophthalmologist. Reasons for an ophthalmic consult included persistence of symptoms among 87.21% of pediatricians and parental/guardian request among 10.5% of pediatricians. According to 45.6% of pediatricians, their knowledge about CNLDO is limited, and 92.2% would like to receive further training on CNLDO. Conclusions: Massage was the main initial treatment for managing CNLDO among pediatricians. The outcomes of this survey indicated that massage fails in fewer than 50% of patients and an ophthalmic referral is required for these cases.
Keywords: Congenital; Lacrimal disease; Massage; Nasolacrimal duct obstruction; Pediatrician